2017
DOI: 10.5032/jae.2017.01014
|View full text |Cite
|
Sign up to set email alerts
|

State Wide Self-Assessment of General Program Standards for Agricultural Education

Abstract: A quality program is the ultimate goal for many secondary agricultural education programs. To ensure quality agricultural education programs, standards were established to measure the extent agricultural education programs in Iowa were implementing standards. Utilizing Ajzen's Theory of Planned Behavior, researchers incorporated the Iowa Council on Agricultural Education standards as an evaluation tool. A census study was conducted in Iowa with high school agricultural education teachers (N = 255) to better un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…It can be concluded the mid-career agriculture teachers who participated in 2016 XLR8 program were more satisfied than dissatisfied with their job. This is consistent with the literature reporting agriculture teachers as being satisfied with their careers (Blackburn et al, 2017;Blackburn & Robinson, 2008;Cano & Miller, 1992;Castillo & Cano, 1999;Chenevey et al, 2008;Gilman, Peake, & Parr, 2012;Kitchel et al, 2012;Sorensen & McKim, 2014;Sorensen et al, 2016a;Walker et al, 2004). Furthermore, there were no significant differences in overall job satisfaction between those contemplating leaving the classroom and those who were not.…”
Section: Conclusion Implications and Recommendationssupporting
confidence: 90%
See 3 more Smart Citations
“…It can be concluded the mid-career agriculture teachers who participated in 2016 XLR8 program were more satisfied than dissatisfied with their job. This is consistent with the literature reporting agriculture teachers as being satisfied with their careers (Blackburn et al, 2017;Blackburn & Robinson, 2008;Cano & Miller, 1992;Castillo & Cano, 1999;Chenevey et al, 2008;Gilman, Peake, & Parr, 2012;Kitchel et al, 2012;Sorensen & McKim, 2014;Sorensen et al, 2016a;Walker et al, 2004). Furthermore, there were no significant differences in overall job satisfaction between those contemplating leaving the classroom and those who were not.…”
Section: Conclusion Implications and Recommendationssupporting
confidence: 90%
“…To establish levels of job satisfaction for teachers, the Brayfield-Rothe job satisfaction index (JSI) (Brayfield & Rothe, 1951), as modified by Warner (1973), was developed. Several variations of this instrument have been utilized within the agricultural education profession to determine levels of job satisfaction of teachers (Blackburn et al, 2017;Blackburn & Robinson, 2008;Cano & Miller, 1992;Castillo & Cano, 1999;Chenevey et al, 2008;Gilman et al, 2012;Walker et al, 2004), and as previously mentioned, agricultural educators are generally satisfied with their careers.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…To address the issue, researchers must identify why agriculture teachers are leaving the profession. Several studies have revealed agriculture teachers as mostly satisfied with their careers (Blackburn, Bunch, & Haynes, 2017;Blackburn & Robinson, 2008;Cano & Miller, 1992;Castillo & Cano, 1999;Chenevey, Ewing, & Whittington, 2008;Gilman, Peake, & Parr, 2012;Kitchel et al, 2012;Sorensen & McKim, 2014;Sorensen, McKim, & Velez, 2016;Walker, Garton, & Kitchel, 2004). With this considered in the context of significant attrition issue, being "mostly satisfied" with one's career does not appear to be enough to prevent attrition.…”
Section: Introductionmentioning
confidence: 99%